Exploring Dengue Transmission Trends, Public Health Challenges, and Intervention Efficacy Among Adolescents in Dhaka City: An Observational Study - Hasan, Md Rakibul; Yusuf, Md. Abdullah; Rogers, Whitney; Muna, Moryom Akter (Asian Journal of Public Health and Nursing, 2025)
Background: Dengue fever remains a major public health threat in Dhaka City, Bangladesh, with adolescents (15–22 years) particularly vulnerable due to high mobility and environmental exposure. This observational retrospective study analyzes fourteen years of dengue trends (2010–2023), comparing them with the August–October 2023 outbreak, which recorded the highest dengue burden in over a decade. The study evaluates disease severity, hospitalization rates, and the effectiveness of targeted public health interventions. Methods: A retrospective hospital-based study was conducted using laboratory-confirmed dengue cases from eight major hospitals in Dhaka City, ensuring adherence to ethical research standards. Comparative analysis between intervention and control regions assessed the impact of vector control programs, awareness campaigns, and healthcare accessibility. Cohen’s d was used to quantify effect sizes, and statistical analyses were performed using SPSS and R software. Results: Dengue cases peaked in September 2023, with a monthly average of 1,250 cases (SD = 300). The overall adolescent prevalence was 15%, with hospitalization rates 15% higher in females than males. Intervention areas showed a 20% reduction in hospital admissions, with a Cohen’s d effect size of 0.6, indicating a moderate impact of public health measures. Lower-income communities faced a 30% higher infection rate, emphasizing disparities in healthcare access and preventive resources. Discussion: Findings reveal that adolescents remain a high-risk group due to urban exposure, limited preventive behaviors, and delayed healthcare access. Comparisons between 2010–2023 and August–October 2023 highlight worsening disease severity, driven by urbanization, climate factors, and inadequate mosquito control. Strengthening real-time surveillance, improving drainage infrastructure, and expanding school-based awareness campaigns is crucial for sustainable dengue control. Conclusion: Targeted public health interventions significantly reduce dengue transmission, but socioeconomic inequalities and urban environmental factors remain major challenges. Sustained vector control, improved urban planning, and enhanced healthcare accessibility are essential for long-term dengue prevention and outbreak preparedness in Dhaka City.